MU'TAZILI TRENDS IN JEWISH THEOLOGY - A BRIEF SURVEY - David Sklare (İslami İlimler Dergisi)
This article presents a brief survey of Jewish Mu‘tazilism, from its beginnings  in  the  late  eighth  or  early  ninth  century  through  the  seventeenth century. Short descriptions of known Jewish Mu‘tazilî authors and their works are provided. We can divide the development of Jewish Mu‘tazilism into  three  periods:  1)  the  early  period  characterized  by  eclecticism  and doctrinal variety; 2) the “classic” period in which the Basran Bahshamiyya school was adopted by both Rabbanites and Karaites; 3) the late period in which epitomes of Mu‘tazilî thought were produced. The article concludes with a brief consideration of Mu‘tazilism in al-Andalus